Kulturowe uwarunkowania skuteczności procesu zmian. Studium przypadku firmy X - Stańda, Andrzej (Cultural influence in the efficiency of the process of changes. The case study of the company X, 2006)
The scientific description analyses the matter of meaning of the culture of the organization in the process of organizational changes, modifications. Author has presented the matter of choosing the methodology of the process of changes that the managers of the process of modifications have to del with the description analyses also the question of the right decision: whether to realize the modifications in order with the rules of technocratic approach or the humanistic one. The case study the real process of changes in the company X reflects the meaning of the culture of organization in the efficiency of the modification.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 586-593